Financing on-the-job training: Shared investment or promotion based system? Evidence from Germany - Markus Pannenberg (Deutsches Institut für Wirtschaftsforschung (DIW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1996)
Though the shared investment hypothesis of human capital theory, i.e. that employers and employees share the costs of and the return on investment in firm-specific human capital, is widely accepted, we know little about the empirical evidence. The paper shows that in German data (1984-1991) there is no empirical evidence for the shared investment hypothesis. Rather we observe that employers use career ladders to protect one-sided investments against opportunistic bargaining. In contrast to these shortcomings we find convincing evidence for human capital theory, analysing the effects of on-the-job training itself on subsequent job mobility, career ladders and wage growth.
Keywords: J24; J31; J62; J63; 330